Analysis and design of wireless power transfer system based on inductor‐capacitor‐capacitor/none magnetic integration compensation circuit. (15th July 2021) - Liu, Zhimeng; Wang, Lifang; Tao, Chengxuan; Li, Shufan; Guo, Yanjie; Li, Fang
Abstract: This paper presents the analysis and design of the wireless power transfer (WPT) system based on the inductor‐capacitor‐capacitor/none (LCC/N) magnetic integration compensation circuit. Compared with the traditional compensation circuits, the proposed LCC/N compensation circuit features the magnetic integration and the secondary side without compensation network, which makes the WPT system more compact. First, the fundamental‐harmonic model considering the coupling relationship among magnetically integrated compensation inductor, transmitter coil, and receiver coil is established. Then, the reactive power and turn‐off current of the inverter, transmission power, and efficiency of the WPT system employing LCC/N compensation circuit are analyzed with varied coupling coefficient and load. Furthermore, based on the characteristics analysis of the LCC/N topology, the parameter design criterion of the LCC/N compensation circuit is given. Finally, the analysis and design of the WPT system based on the LCC/N magnetic integration compensation circuit are verified by simulations and experiments. The results show that the characteristics analysis of the WPT system employing the LCC/N compensation circuit is accurate, the inverter can realize zero‐voltage‐switch (ZVS) and the WPT system can achieve the rated power of 1 kW under different offset distances of coils and reach the maximum efficiency of 95.3%. Abstract : This paper presents the analysis and design of the wireless power transfer (WPT) system based on the inductor‐capacitor‐capacitor/none (LCC/N) magnetic integration compensation circuit. Compared with the traditional compensation circuits, the proposed LCC/N compensation circuit features the magnetic integration and the secondary side without compensation network, which makes the WPT system more compact.